Analisa Kerusakan Pompa Dengan Menggunakan Metode FMEA ( Study Kasus PDAM Surya Sembada IPAM Ngagel 1 Rumah Pompa Utara) - Achmad Ryan, Nur Sahrudin; Stighfarrinata, Rizky (Jurnal Teknologi dan Manajemen Sistem Industri, 2022)
The location of the research carried out in writing the journal here is PDAM Surya Sembada, Surabaya City. PDAM Surya Sembada Surabaya City is one of the companies owned by the Regional Government (PEMDA) whose role is in processing and providing clean water to serve the people of Surabaya city, taking raw water taken from the Jagir River to then be processed and then distributed to customers. At this time the machines that are used operationally at PDAM are fairly old and therefore machines often experience damage problems. One of the methods used to anticipate problems in this case is the FMEA method. This method is used to anticipate an small problems before big problems. The steps used in this method include processing damage data in 2021, identifying the type of damage, results of the identification process and finally conclusions and suggestions. The data collection process is obtained from the results of observations and interviews or discussions with related parties between managers, supervisors and maintenance staff.